The efficacy of L-carnitine treatment in dilated cardiomyopathy - Donder, E.; Colak, R.; Karaoglu, A.; Ayhan, O.; Ozkan, Y. (My University, 1998)
This study was carried out to investigate clinical effects of treatment with the supplementation of L-carnitine in cases with dilated cardiomyopathy. B Mode, M-Mode, and continuous Doppler echocardiograms were applied with standard techniques in totally 28 patients assessed before treatment with L- carnitine and at the 1(st), 5(th), 10(th), 30(th), and 60(th) days of the treatment. The diameter of the left ventricular end-systolic and end- diastolic have decreased with L-carnitine treatment (p<0.05). While an increase was observed in the interventricular septum motion (p<0.0001); decrease was observed in the left ventricular end-systolic and end-diastolic volumes (p<0.05), and an increase was also observed in the ejection fraction, myocardial fractional shortening, and velocity of circumferential fiber shortening (p<0.05). No significant change occurred at the diastolic function of the left ventricle. As a conclusion, supplementation of L-carnitine to the conventional therapy, dilated cardiomyopathy treatment can give successful clinical result in refractory cases.
Keywords: Dilated Cardiomypopathy; Doppler Echocardiography; L-Carnitine